Ecosystem Services Assessment after 13 Years Restoration Program in the Janitri Water Spring Conservation Area at Batu City - Abban Putri Fiqa; Titut Yulistyarini; Endang Arisoesilaningsih (Graduate Program, 2018)
Janitri water springs conservation area was restored by local government on 2004, with local and others plants based on recommendation of community around the area. The objective of the research is to evaluate the restoration success by comparing the vegetation, soil biophysics condition and ecosystem services provided in the restored area, secondary forest, and agricultural land as a positive and negative control. Result shows that the diversity index for trees, sapling and groundcover in the restored area (tree: 1.55; sapling: 2.61; groundcover: 2.71) have the higher value than in the secondary forest (tree: 0.79; sapling: 2.30; groundcover: 2.33), although its density value is lower than in the secondary forest. The vegetation quality in the restored area is much better than in the agricultural land. Soil and bulk density in the restored area are higher than in the secondary forest and lower than in the agricultural land. Infiltration rate in the three areas was not significantly different, however secondary forest has the highest value, while the C-stock in the secondary forest almost four times than in the restored area. The restoration that have been done, has already increase the diversity, soil biophysics characteristic, and its ecosystem services in the restored area, however the restoration process should be monitored frequently to keep the restoration activity run as planned.Keywords: Ecosystem services, Janitri water spring, Restoration, Soil biophysics, Vegetation